Reconnection with Asi Kéyi: Healing Broken Connections' Implications for Ecological Integrity in Canadian National Parks - Nakoochee, Roberta (University of Guelph, 2018)
The establishment of protected areas has long served to displace Indigenous peoples from their traditional territories, undermining Indigenous knowledge systems and the ecology of which they are a part. In the Yukon Territory, Kluane National Park recognizes Southern Tutchone ‘Cultural Reintegration’ as an indicator of ecological integrity. The park thus hosted Healing Broken Connections, a project managed in partnership with the Champagne and Aishihik First Nations and Kluane First Nation which sought to address 50 years of First Nation displacement from the park. The purpose of this thesis is to identify how reconnection to land can be achieved and how well this was reflected within the activities of the project. Results indicate that Healing Broken Connections strengthened the partners’ nation-to-nation relationship and began a healing process between people and land inherent to the park’s management priorities but also identified key factors that need addressing in order for healing to continue. Canadian Conservation in Global Context: Intersections with Africa and Asia Social Sciences and Humanities Research Council of Canada Ontario Graduate Scholarship